Sleep quality, anxiety, symptoms of depression, and caregiver burden among those caring for patients with Dravet syndrome: a prospective multicenter study in Germany - Maltseva, Margarita; Schubert-Bast, Susanne; Zöllner, Johann Philipp; Bast, Thomas; Mayer, Thomas; von Spiczak, Sarah; Ruf, Susanne; Trollmann, Regina; Wolff, Markus; Hornemann, Frauke; Klotz, Kerstin A.; Jacobs, Julia; et al. (Orphanet Journal of Rare Diseases, 2023)
Background: This study measured sleep quality among caregivers of patients with Dravet syndrome (DS) and assessed the impacts of mental health problems and caregiver burden on sleep quality. Methods: This multicenter, cross-sectional study of patients with DS and their caregivers throughout Germany consisted of a questionnaire and a prospective 4-week diary querying disease characteristics, demographic data, living conditions, nocturnal supervision, and caregivers’ work situations. Sleep quality was assessed using the Pittsburgh Sleeping Quality Index (PSQI). The Hospital Anxiety and Depression Scale (HADS) and the Burden Scale for Family Caregivers (BSFC) were used to measure anxiety, symptoms of depression, and caregiver burden. Results: Our analysis included 108 questionnaires and 82 four-week diaries. Patients with DS were 49.1% male (n = 53), with a mean age of 13.5 ± 10.0 years. Caregivers were 92.6% (n = 100) female, with a mean age of 44.7 ± 10.6 years. The overall mean PSQI score was 8.7 ± 3.5, with 76.9% of participants (n = 83) scoring 6 or higher, indicating abnormal sleep quality. The HADS for anxiety and depression had overall mean scores of 9.3 ± 4.3 and 7.9 ± 3.7, respectively; 61.8% and 50.9% of participants scored above the cutoff value of 8 for anxiety and depression, respectively. Statistical analyses revealed caregiver anxiety levels and patients’ sleep disturbances as major factors influencing PSQI scores. The overall mean BSFC score of 41.7 ± 11.7 indicates a moderate burden, with 45.3% of caregivers scoring 42 or higher. Conclusions: Sleep quality is severely affected among caregivers of patients with DS, correlating with anxiety, comorbidities, and patients’ sleep disturbances. A holistic therapeutic approach should be implemented for patients with DS and their caregivers, focusing on the sleep quality and mental health of caregivers. Trial registration: German Clinical Trials Register (DRKS), DRKS00016967. Registered 27 May 2019, http://www.drks.de/DRKS00016967
CRIS-Team Scopus Importer:2023-05-12
Keywords: Encephalopathy; Epilepsy; Quality of life; Seizure